Climate change and its impact on the population of Northern Lima - Erika Gabriela Ramos-Liza; Johnathan Burgos-García; Herly Handy Vega-Trujillo; Zaira Loami Solis-Aranda; William Joel Marín-Rodriguez; Luis Alberto Baldeos-Ardían; Flor de María Lioo-Jordán; Santiago Ernesto Ramos Y-Yovera; José Luis Ausejo-Sánchez (EAI Endorsed Transactions on Energy Web, 2023)
Introduction: The impact caused by climate change at present presents a high risk in the health field with consequences in the social and environmental fields. For example, there has been an increase in illnesses and social concern due to the lack of information among citizens.